Reconstructing the Legal Framework of Standard Clauses in Insurance Agreements for Consumer Protection - Wawan Suryadinata; Naya Amin Zaini; Wieke Dewi Suryandari (Journal of World Science, 2024)
Standard clauses in insurance agreements often result in legal certainty and adequate consumer protection. This study aims to reconstruct the legal framework governing standard clauses in insurance agreements to enhance consumer protection and ensure legal certainty. Using a normative juridical research method, the study adopts a statute and conceptual approach. Data were collected from legislative texts, legal literature, and case studies involving disputes over standard clauses in insurance agreements. The analysis focuses on identifying weaknesses in the current legal framework and proposing solutions to address them. The results reveal that the unilateral drafting of standard clauses by insurers often diminishes consumer rights and creates imbalances in contractual relationships. This research highlights the need for simplification of legal language, active consumer participation in drafting agreements, and stricter regulatory oversight. The study contributes to developing a fairer insurance policy framework, promoting transparency, accountability, and consumer trust in the insurance industry.